Pengaruh Motivasi, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada PT.Randi Cones Malang) (UNIVERSITAS ISLAM MALANG, 2021)
AbstractTo determine the effect of work motivation, work discipline, and work environment on employee performance at PT. Randi Cones Malang. This research was conducted on 33 respondents. The data analysis technique used multiple linear regression.The results of descriptive analysis in this study indicate that employees of PT. Randi Cones perceive all research, namely work motivation, work discipline, work environment, and employee performance. work motivation, work discipline, and work environment simultaneously influence the performance of employees of PT. Randi Cones Malang. Keywords: Work Motivation, Work Discipline, Work Environment, and EmployeePerformance